2013
DOI: 10.3168/jds.2013-7106
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the bovine milk proteome through extensive fractionation

Abstract: Bovine milk is an agricultural product of tremendous value worldwide. It contains proteins, fat, lactose, vitamins, and minerals. It provides nutrition and immunological protection (e.g., in the gastrointestinal tract) to the newborn and young calf. It also forms an important part of human nutrition. The repertoire of proteins in milk (i.e., its proteome) is vast and complex. The milk proteome can be described in detail by mass spectrometry-based proteomics. However, the high concentration of dominating protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…This investigation was based on the results previously reported for proteins identified in colostrum (Nissen et al, 2012) and milk (Nissen et al, 2013). Both publications contain a thorough description of the procedures of fractionation and analysis; therefore, only a brief summary and an illustration of the fractionation and sample processing is presented here (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This investigation was based on the results previously reported for proteins identified in colostrum (Nissen et al, 2012) and milk (Nissen et al, 2013). Both publications contain a thorough description of the procedures of fractionation and analysis; therefore, only a brief summary and an illustration of the fractionation and sample processing is presented here (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was determined before pooling the samples (on a volume or protein weight basis) and in NF and fractions F1 to F5 before proteome analysis (Nissen et al, 2012(Nissen et al, , 2013. Further, colostrum and milk samples were collected and analyzed in a diagnostic dairy laboratory (Eurofins Steins Laboratory) for total protein content.…”
Section: Protein Detection and 2d-lc-ms/msmentioning
confidence: 99%
See 2 more Smart Citations
“…Nissen et al (2012) identified 403 minor proteins in colostrum using 2D-LC-MS/MS, which, to the authors' knowledge, is the most comprehensive characterisation to date of whey proteins in colostrum. In a follow-on study, Nissen et al (2013), also using 2D-LC-MS/MS, identified a total of 742 minor proteins in milk; however, 366 of these proteins were identified only in one replicate and are therefore regarded as tentative results.…”
Section: Proteinmentioning
confidence: 99%